2016
DOI: 10.1177/0738894215577556
|View full text |Cite
|
Sign up to set email alerts
|

The domestic consequences of international over-cooperation: An experimental study of microfoundations

Abstract: BackgroundMental health recovery has been referred to as a new paradigm. In English speaking countries it is clear that it has been able to influence the thinking of a range of stakeholders and has the potential to transform the perception and experience of service users, service providers and staff. AimThis study aimed to capture the views of attendees on mental health recovery at the 2 nd worldHearing Voices Congress and Festival in Nottingham, England

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 77 publications
0
6
0
Order By: Relevance
“…Studies such as Sigelman and Sigelman (), Cuckierman and Tommasi (), and Cowen and Sutter () assume that the “election” or “poll” happens before the response by the other state is known and thus before the policy can be deemed successful or not. More recent work (e.g., Clare ; Colaresi ; Davies and Johns ; Schultz ) takes into consideration that voters might update their opinions based on the adversary's reaction. Interestingly, these studies formulate quite different expectations about how voters respond to success and failure of conciliatory policies by hawks and doves.…”
Section: The Theoretical Basis Of the Hawk's Advantagementioning
confidence: 99%
See 1 more Smart Citation
“…Studies such as Sigelman and Sigelman (), Cuckierman and Tommasi (), and Cowen and Sutter () assume that the “election” or “poll” happens before the response by the other state is known and thus before the policy can be deemed successful or not. More recent work (e.g., Clare ; Colaresi ; Davies and Johns ; Schultz ) takes into consideration that voters might update their opinions based on the adversary's reaction. Interestingly, these studies formulate quite different expectations about how voters respond to success and failure of conciliatory policies by hawks and doves.…”
Section: The Theoretical Basis Of the Hawk's Advantagementioning
confidence: 99%
“…A recent experimental study found that British voters generally disapproved of policy failures but were especially likely to punish leaders who they thought had over‐cooperated with an adversary; however, this study does not consider leader type (Davies and Johns ).…”
mentioning
confidence: 96%
“…In his empirical analysis of leaders’ tenures, Colaresi (2004) finds that dovish leaders are more likely to lose power than their hawkish counterparts. Supporting this logic, Davies and Johns (2016: 343) use a survey experiment and find that “a hawkish failure wins more public sympathy than a failed inducement.” The population in rival states might request a more coercive crisis behavior to restore a sense of national pride that has been challenged by repeated violence (Crescenzi et al, 2007: 657). Alternatively, military action might be more popular because using force might be considered as a simpler solution to ongoing violence (Davies and Johns, 2016: 347).…”
Section: Research On Crisis Escalation and Precrisis Hostilitiesmentioning
confidence: 99%
“…Supporting this logic, Davies and Johns (2016: 343) use a survey experiment and find that “a hawkish failure wins more public sympathy than a failed inducement.” The population in rival states might request a more coercive crisis behavior to restore a sense of national pride that has been challenged by repeated violence (Crescenzi et al, 2007: 657). Alternatively, military action might be more popular because using force might be considered as a simpler solution to ongoing violence (Davies and Johns, 2016: 347). What is common to these explanations is that a history of persistent violence increases public expectation and pressure for violent escalation during crises.…”
Section: Research On Crisis Escalation and Precrisis Hostilitiesmentioning
confidence: 99%
“…28.Brutger 2017; Davies and Johns 2013, 2016; Fearon 1994; Kertzer and Brutger 2016; Levendusky and Horowitz 2012; Potter and Baum 2014; Schultz 2001; Tomz 2007a; Trager and Vavreck 2011; Weeks 2008.…”
mentioning
confidence: 99%